Creating a self-directed learning environment : standards-based and social-emotional learning - Mullen, Greg (Educator) (Corwin, 2020)
Educate the whole child-improve the whole school. Implementing evidence-based and innovative teaching practices can feel like juggling: If you have standards-based learning in one hand and social-emotional learning in the other, what do you do with cognitive development? This book shows you how to balance all 3, combining these concepts into manageable, realistic plans for success. In clear, easy-to-follow language, master teacher and educational expert Greg Mullen introduces a flexible, three-tiered, visual framework designed for schoolwide collaboration. He also offers: • An integrated philosophy focused on self-directed learning and the whole child • Research sourced from CASEL and state programs and initiatives • Attention to academic inclusion, behavior intervention, and classroom management • Numerous illustrations, tables, and graphics • Tools and supplemental resources for implementation Make innovation work for your school. With this guide, you and your colleagues will build on your strengths, discover the potential of your existing programs, and implement smart changes that make a real difference for students.